Standard Operating Procedures (SOPs) for non-invasive multiple biomarkers detection in an academic setting: A critical review of the literature for the RENOVATE study protocol. (May 2023) - Dameri, Martina; Cirmena, Gabriella; Ravera, Francesco; Ferrando, Lorenzo; Cuccarolo, Paola; Stabile, Mario; Fanelli, Giuseppe Nicolò; Nuzzo, Pier Vitale; Calabrese, Massimo; Tagliafico, Alberto; Ballestrero, Alberto; Zoppoli, Gabriele
Abstract: Liquid biopsy has the potential to drastically change clinical practice, paving the way to a novel non-invasive approach for cancer diagnosis and treatment. One of the limitations for the implementation of liquid biopsy in clinical practice is the lack of shared and reproducible standard operating procedures (SOPs) for sample collection, processing and storage. Here, we present a critical review of the literature focusing on the available SOPs to guide liquid biopsy management in research settings and describe SOPs that our laboratory developed and employed in the context of a prospective clinical-translational trial (RENOVATE, NCT04781062). The main aim of this manuscript is to address common issues, towards the implementation of interlaboratory shared protocols for optimized preanalytical handling of blood and urine samples. To our knowledge, this work is one of the few up-to-date, freely available comprehensive reports on trial-level procedures for the handling of liquid biopsy. Graphical Abstract: ga1 Highlights: Liquid biopsy may represent a feasible non-invasive alternative to tissue biopsy. The development of standard operating procedures (SOPs) for liquid biopsy management is essential for clinical purposes. During the RENOVATE trial (NCT04781062) we developed a set of SOPs for efficient blood and urine collection and processing. Detailed sharing of SOPs may be useful to simplify the adoption of common protocols for the handling of liquid biopsy. Here we present a review of the literature, compared with our experience, as a reference tool for the scientific audience.